Mindfulness in education: the case of Singapore. (2nd January 2018) - Khng, Kiat Hui
ABSTRACT: Since the formal introduction of mindfulness-based practices (MBPs) into clinical settings in the late 1970s, a growing body of research has demonstrated their benefits in diverse settings, from clinical programmes, business and sports, to education. Along with the development of standardised mindfulness-based programmes in the areas of clinical therapy, counselling, self-enhancement, and corporate training, standardised curricula for school-based mindfulness have become available, and are gaining popularity around the world. However, the adoption of MBPs in schools in Singapore, whether formally or informally, seems to be lagging behind that of counterparts in countries such as Australia, the UK, and the USA. This paper describes the current state of mindfulness-in-education in Singapore, focusing on the extent and ways in which MBPs are incorporated into the local school setting. Included are brief introductions to mindfulness, mindfulness in education, and mindfulness-in-education research in Asia. Local research and continuing efforts in the area, as well as challenges and future directions are discussed.